SOSIALISASI PEMANFAATAN MEDIA SOSIAL UNTUK PEMASARAN DAN PENGAWASAN KEBERSIHAN PRODUK PEMPEK DI TANGGO RAJO CINDO PALEMBANG - Sutinah, Sutinah; Hakim, Arif Rahman; Islamy, Diah Putri; MK, Samsul; Nuraina, Kurnia; Fajri, Ahmad (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STISIPOL Candradimuka, 2024)
The STISIPOL Thematic Community Service Program on Sustainable Tourism 2024 focuses on the development of culinary tourism in Palembang, particularly pempek, which is not only renowned nationally but also attracts international tourists. Pempek, as a cultural icon of Palembang, plays a significant role in attracting tourists and boosting the local economy. Although pempek MSMEs (Micro, Small, and Medium Enterprises) have contributed significantly to Palembang's economy, they still face various challenges, especially in the aspect of digital marketing. This community service program aims to provide socialization on digital marketing to pempek MSME actors in Kampung Kreatif Tanggo Rajo Cindo, 7 Ulu Village, Palembang. Besides marketing, the program also highlights the importance of hygiene supervision in the processing of culinary products in accordance with applicable hygiene and sanitation standards. The program's implementation methods include an initial survey to identify the challenges faced by MSMEs, socialization on marketing through social media, and cleanliness in pempek processing. The results of this activity show an increased understanding among MSME actors of the use of social media as a marketing tool and the importance of cleanliness in maintaining product quality. Therefore, this program is expected to enhance the competitiveness of pempek MSMEs in 7 Ulu Village, Palembang, and promote more.